Characterization and thermal kinetic analysis of pineapple leaf fibers and their reinforcement in epoxy. (April 2019) - Jain, Jyoti; Jain, Shorab; Sinha, Shishir
The progress in the development of composites with natural fibers for various applications in different sectors witnesses remarkable success worldwide in the last decade. Among the various natural fibers existing worldwide, pineapple leaf fibers (PALFs) possess remarkable mechanical properties because of the maximum content of cellulose (∼80%) among all natural fibers. In spite of having few limitations such as hydrophilicity, its advantages such as low cost, low weight, and biodegradability overweigh their limitations. The PALFs are poorly reported in the literature as a reinforcement in epoxy material. Bagasse, wheat straw, and coir have been successfully reinforced with epoxy resin; but inspite of having highest tensile strength among all natural fibers, PALF's are seldom used. PALF has been characterized chemically, morphologically, and thermally. Using thermal analysis, the models were fitted to calculate its activation energies at different fraction levels using different heating rates. PALF epoxy composites have been prepared using the hand layup method. The effect of fiber loading has also been studied for morphological, chemical, mechanical, and thermal properties of composites. Composites with 10% fiber loading have better mechanical properties in comparison to composites with other fiber loading. Scanning electron microscopic micrographs of fractured surfaces have been analyzed for all fiber loading composites, and the results have been successfully studied linking the stated work of other distinguished researchers of this arena.